(untitled) (Bangladesh Heart Journal, 2021)
Introduction: Warfarin is recommended following mechanical valve replacement to prevent thromboembolic complications. A combination of warfarin and aspirin may further reduce thromboembolic events in these patients. This study was designed to evaluate safety and efficacy of combined low dose aspirin and warfarin therapy following mechanical mitral valve replacement. Materials and Methods: Purposively selected 99 patients who underwent mechanical mitral valve replacement were divided into two groups. Patients of Group A (n=50) received combined low dose aspirin (75mg) and warfarin. Patients of Group B (n=49) received conventional dose of warfarin alone. International normalized ratio (INR) was targeted 1.8-2.4 for group A Patients and 2.5-3.5 for group B Patients. Post-operatively INR, thromboembolic events, anti-coagulation related haemorrhage and other morbidity and mortality were registered in both groups. Result: Patients were followed up postoperatively for 9 months. The mean dose of warfarin in group A and group B was 4.36 ± 0.31 mg and 5.57±0.52 mg respectively (p<0.001). The overall mean INR of two groups of patients were statistically different (P<0.001) with low INR in group A (2.19±0.13) patients compared to group B (3.03±0.31). The thromboembolic events in group A (0.02/patient year) were lower than those in group B (0.08/Patient year). There was no statistically significant (p=0.362) difference in bleeding episodes between two groups but data indicate proportion of minor bleeding manifestations were higher in patients treated with warfarin plus aspirin group. Conclusion: Following mechanical mitral valve replacement, a combination of aspirin (75mg) and low dose warfarin with an aim to maintain INR between 1.8 and 2.4 (lower than recommended 2.5-3.5) may provide satisfactory outcomes in term of thrombosis, embolism and bleeding without increase in mortality. Bangladesh Heart Journal 2021; 36(1): 24-31